Effect of Medial Arch Support Foot Orthosis on Pressure Distribution and Peak Pressure in Women with Hallux Valgus - Fitri, Rahma Maulida; Triyani, Triyani; Lestari, Tri Riana; Silmia, Ana (Poltekkes Kemenkes Jakarta I, 2024)
Background: Hallux Valgus (HV) entails a deformity of the hallux, resulting in heightened pressure on both the hallux and forefoot. One potential intervention involves utilizing foot orthoses with medial arch support. Aims: This study aimed to assess the impact of medial arch support foot orthoses on pressure distribution and peak pressure among women exhibiting mild to moderate hallux valgus. Methods: The research employed a quasi-experimental design, employing a one-group pretest-posttest methodology with 16 participants. Data collection involved recording pressure distribution and peak pressure via foot scans before and after one month of utilizing Medial Arch Support Foot Orthoses. Parametric analysis utilized a paired T-test. Results: The findings indicated a significant reduction in peak pressure, particularly in toe 1 and the metatarsal region (p < 0.005). However, there were no notable alterations in pressure distribution (p > 0.005), although a shift in mean pressure distribution from 21.94 to 22.63 was observed in the right forefoot. Conclusion: Medial arch support foot orthoses demonstrated efficacy in altering pressure distribution and mitigating peak pressure, thereby presenting as a viable intervention for individuals with hallux valgus. Future research should consider incorporating additional variables, such as spatiotemporal differences, both pre- and post-utilization of medial arch support foot orthoses.